Predicting the 1000 m rowing ergometer performance in 12-13-year-old rowers: The basis for selection process? - Mikulic, P.; Ruzic, L. (Journal of Science and Medicine in Sport, 2008)
Performance-predictive parameters have been established for rowers representing different quality levels, sexes, weight categories and classifications, but none have been designed for very young rowers (age <14). The objective of this study was to predict 1000-m rowing ergometer performance based on 12 anthropometric and six physiological variables in 48 male rowers (age range 12.0-13.9 year; mean ± S.D. 12.94 ± 0.61) and to determine the key parameters that would perhaps provide a scientific basis for talent identification and the selection process in rowing. The subjects completed an incremental maximal treadmill test. Their body height (r = -0.79), body mass (r = -0.60), lean body mass (r = -0.82), leg length (r = -0.72), arm length (r = -0.71), bicristal diameter (r = -0.63), biacromial diameter (r = -0.73), upper arm girth (r = -0.34), forearm girth (r = -0.63), thigh girth (r = -0.29), calf girth (r = -0.54), maximal oxygen uptake (in L/min, r = -0.89; and in mL/kg/min, r = -0.36), maximal ventilation (r = -0.77), and oxygen uptake at ventilatory anaerobic threshold (r = -0.87) correlated with 1000-m time (p < 0.05), while percent body fat, percent of maximal oxygen uptake at ventilatory anaerobic threshold and maximal lactate did not. Performance correlated significantly with age (r = -0.46; p < 0.01), so it was important to consider this effect in the resulting regression models. Multiple regression procedures indicated that the model comprising anthropometric and physiological variables combined best predicts performance (R2 = 0.85), followed by models that comprised physiological (R2 = 0.80) and anthropometric (R2 = 0.76) variables alone. In conclusion, in rowers aged 12-13 year a higher aerobic capacity (as measured by maximal oxygen uptake in L/min), and a larger body size are beneficial for performance over 1000-m rowing ergometer distance.